Patient-reported outcomes: an overview of applications - S. M. Mukhina; E. V. Orlova (Реальная клиническая практика: данные и доказательства)
This article focuses on patient-reported outcomes (PROs) and their role in decision making in patient-centred healthcare. Let»s look at how PRO can be used in clinical trials, to evaluate the effectiveness of treatment, to validate a claim on a product label by regulatory authorities, and in clinical practice to monitor patient conditions.